Analysis of Backhand Stroke Ability among Table Tennis UKM Members - Tafonao, Tison Rahmat; Sugiarto, Bambang Gatot; Zakaria, Dhani Agusni (STKIP Paasundan Press, 2025)
Thisstudy aimsto analyze the level of backhand stroke ability among members of the Table Tennis UKM at STKIP Pasundan Cimahi. This research uses a quantitative method with a survey approach, employing a skill test instrument in the form of a backhand backboard test. The population consisted of all members of the Table Tennis UKM, with a total sample of 15 participants. The results showed that 60% of participants were in the